2013
DOI: 10.2308/jeta-50712
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Enterprise Resource Planning (ERP) Systems on the Audit Report Lag

Abstract: Prior research has shown that the implementation of ERP systems can significantly affect a firm's business operations and processes. However, scant research has been conducted on the relationship between ERP implementation and the timeliness of external audits, such as audit report lags. While some of the alleged benefits of ERP are closely related to removing impediments contributing to audit report lags, others argue that the complex mechanisms of ERP systems create greater complexity for control and audit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The auditors' busy season would, therefore, be expected to coincide with audit delays. Prior studies have found that “busy‐season” clients result in high levels of workload compression, and thus are likely to have a larger audit delay (Ghosh & Tang, ; Harjoto et al, ; Kim, Nicolaou, & Vasarhelyi, ; Knechel & Payne, ; Knechel & Sharma, ; Lee, Mande, & Son, ; Whitworth & Lambert, ). Alternatively, auditors can offset the pressure of workload from the busy audit season by additional overtime, so that the maximum number of clients can be served within a limited available schedule, which can lead to a shorter ARL.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The auditors' busy season would, therefore, be expected to coincide with audit delays. Prior studies have found that “busy‐season” clients result in high levels of workload compression, and thus are likely to have a larger audit delay (Ghosh & Tang, ; Harjoto et al, ; Kim, Nicolaou, & Vasarhelyi, ; Knechel & Payne, ; Knechel & Sharma, ; Lee, Mande, & Son, ; Whitworth & Lambert, ). Alternatively, auditors can offset the pressure of workload from the busy audit season by additional overtime, so that the maximum number of clients can be served within a limited available schedule, which can lead to a shorter ARL.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…There are many previous Research on enterprise resource planning such as (Morris, 2011), Kim, Nicolaou and Vasarhelyi (2013), Catalya and Hadiprajitno (2014), Puspandoyo T. (2015), Rahmawati R. and Zulkarnaini (2018), proven that with SOX provisions, companies that implement ERP systems have increased their internal control. This research results.…”
Section: Grafic 1 -Before and After Erp Source: Fit Labs Telkom Universitymentioning
confidence: 99%
“…The results of Soral and Jain (2011) show that the use of technology will improve the quality of auditing and internal control systems in organizations (Doyle and McVay, 2007;Foster and Shastri, 2013). Kim, Nicolaou, and Vasarhelyi (2013) observed that auditing conducted by ERP allows these things: recording events on the network-wide audit trail, detecting misuse and unauthorized activity, reviewing access patterns and history access from individuals and objects, find attempts to bypass protection mechanisms, and find extended use of privileges that occur when users change their identities (Dahlén and Elfsson, 1999;Brown, 2003;Brazel, 2005) Internal control over the firms will not necessarily be better (Abdel-Khalik, 1993;Boynton, Johnson, and Kell, 2004). Not all internal controls in the firm can function properly, and this occurs due to the firm's internal control components weaknesses (Sawyer, 2012).…”
Section: Research Hypothesismentioning
confidence: 99%
“…ERP is an information technology that is able to integrate all cross-division transaction data using a database (Sumner, 2013). Dechow and Mouritsen (2005), Morris (2011), Kim et al (2013) explained that firms that had implemented ERP reported less material internal control weaknesses than firms that had not implemented ERP-from that perspective, it is essential to separate the internal control into general and specific. Internal control, in general, is a form of general control.…”
Section: H1: Firms That Have Implemented Erp Reported Fewer Materials mentioning
confidence: 99%